Mathematical model of the recovery and quality of Virgin Coconut oil - Llacuna, Neneth Lilian G. (2005)
Studies on benefits of virgin coconut oil (VCO) have already been conducted. However, a study on the behavior of VCO has yet been done. This study aimed to develop a mathematical model that would describe the behavior of the VCO in terms of its recovery and quality, across the days of storage of coconut and fermentation time of coconut milk with coconut water. The days of storage considered are 0, 3, and 6 days. The duration of fermentation are 16, 20, and 24 hours. The data were analyzed using f-test and DMRT. The analysis for the effect of interaction between factors indicates that the integration is not significant to the percentage recovery and pH level of VCO. However, the effect of the interaction is significant to the FFA content. Bicubic spline interpolation was used to approximate values of the percentage recovery, pH, and free fatty acid content for the points not tested in the experiment but lie within the interval of the combinations of factors tested. To look for the optimal solution among the combinations, the idea of multiple objective decision making (MODM) was utilized. The optimization problem was then solved using the Solver add-in of Microsoft Excel. Based on the mathematical model, the optimal combinations for VCO are storing coconuts for 3 days and 16 hours of fermentation of coconut milk, and storing for 4 days and 16 hours for fermentation. both of the combinations are considered as optimal since they are nondominated solutions. Since these combinations lie on the boundaries of the interval of values tested for this study, it is recommended that a study on exploration of duration of fermentation less than 16hours for VCO production be performed.
Thesis (BS Applied Mathematics) -- University of the Philippines Mindanao, 2005